FRI0031 Naturally occurring antibodies against different IFN-alpha subtypes are observed in some SLE patients, and may impact the IFN gene signature and disease activity. (23rd January 2014) - Ross, C.; Lundsgaard, D.; Fleckner, J.; Olferiev, M.; Kirou, K.; Wiberg, C.; Bendtzen, K.; Frederiksen, K.; Crow, M.K.
Abstract : Background: Upregulation of mRNA IFN-alpha activity (IFN signature) has been demonstrated in some patients with systemic lupus erythematosus (SLE). Based on this observation anti-IFN-alpha mAbs are currently being developed for the treatment of SLE. Interestingly naturally occurring antibodies towards IFN-alpha have previously been demonstrated in a small fraction of healthy individuals, in therapeutic IgG preparations and in patients with inflammatory disorders. Objectives: Recently naturally occurring antibodies against a single IFN alpha subtype were observed in SLE patients. A high level of such anti-IFN antibodies could theoretically affect the IFN gene signature and clinical disease activity. Therefore we carried out a longitudinal study of IFN activity, anti-IFN antibodies (frequency, titre, neutralizing capacity, specificity) and disease activity in a cohort of SLE patients. Methods: Peripheral blood mononuclear cells (PBMC) and plasma samples were collected over an average of 6 visits (range 2-12) from 23 SLE patients (median SLEDAI score at initiation 6 (range 0-35) and 5 healthy donors. Patients were followed from 197 to 812 days. Plasma levels of autoantibodies towards a mixture of IFN-alpha 1, 2- and 8 or the individual subtypes were measured by radioimmunoassay, and 44 other autoantibodies were evaluated in a multiplex luminex system by Rules-Based-Medicine. The mRNA IFN signature was deduced from full transciptome analyses in PBMCs using Human Genome U133 Plus 2.0 arrays and RT-PCR. Results: In healthy donors no autoantibodies towards IFN-alpha were detected; in alignment with historic data where the frequency is 3-5/1.000 individuals. In contrast, we detected specific anti-IFN-alpha antibodies in 4/23 (17%) of the patients. In three of these, the autoantibodies were present throughout the study while the last patient developed autoantibodies between visits 5 and 6. In one of the patients very high titres of antibodies to the IFN mixture and against the individual IFN subtypes were demonstrated while the other patients had lower titres. The antibodies in the highly positive patient demonstrated increasing neutralizing capacity throughout the study. The four anti-IFN-alpha-positive patients did not demonstrate an increased level of other autoantibodies when compared to anti-IFN antibody negative patients. A composite score of 12 well characterized IFN-alpha inducible genes (IFN signature) was defined. A 1.2 to 4-fold fluctuation in the IFN-score was observed over time in the individual patients. The patient with high levels of neutralizing anti-IFN antibodies showed significantly reduced IFN signature activity during the study. Conclusions: Anti-IFN autoantibodies are present in a subset of SLE patients. An association of anti-IFN alpha 4 antibodies and disease activity has previously been reported, and our study confirms this for additional IFN-alpha subtypes. Naturally occurring autoantibodies against IFN-alpha could affect treatment outcome following anti-IFN mAb therapy. Disclosure of Interest: C. Ross Shareholder of: Novo Nordisk, Employee of: Novo Nordisk, D. Lundsgaard Shareholder of: Novo Nordisk, Employee of: Novo Nordisk, J. Fleckner Shareholder of: Novo Nordisk, Employee of: Novo Nordisk, M. Olferiev: None Declared, K. Kirou: None Declared, C. Wiberg Shareholder of: Novo Nordisk, Employee of: Novo Nordisk, K. Bendtzen: None Declared, K. Frederiksen Shareholder of: Novo Nordisk, Employee of: Novo Nordisk, M. Crow: None Declared